2018
DOI: 10.1002/jsfa.9425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary marigold extract on lutein content, yolk color and fatty acid profile of omega‐3 eggs

Abstract: BACKGROUND: Lutein is a plant pigment very important for eye health in humans. Its bioavailability in humans is better from egg yolk than from dietary supplements. The aim of this research was to determine the influence of lutein (marigold extract powder) supplemented to laying hens' feed rich in omega-3 fatty acids on the content of lutein, fatty acid profile in egg yolks and yolk color. The diets that contained 5% of oils as a source of omega-3 fatty acids were supplemented with 0, 1 and 2 g kg −1 of marigol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…More recently, results obtained with an enrichment of the diet with microalgae or linseeds have revealed the potential of these compounds to increase the content of yolk in n-3 fatty acids (more than 3- and 4-fold increase, respectively) [145]. A similar trend in increasing the polyunsaturated content of yolk was observed with marigold extract powder [146], Schizochytrium microalgae [147], prebiotic and probiotic combination [148], etc. To conclude, it is relatively easy to enrich the egg in some unsaturated fatty acids, of interest for human health.…”
Section: Factors Affecting Egg Qualitymentioning
confidence: 75%
“…More recently, results obtained with an enrichment of the diet with microalgae or linseeds have revealed the potential of these compounds to increase the content of yolk in n-3 fatty acids (more than 3- and 4-fold increase, respectively) [145]. A similar trend in increasing the polyunsaturated content of yolk was observed with marigold extract powder [146], Schizochytrium microalgae [147], prebiotic and probiotic combination [148], etc. To conclude, it is relatively easy to enrich the egg in some unsaturated fatty acids, of interest for human health.…”
Section: Factors Affecting Egg Qualitymentioning
confidence: 75%
“…The composition of fatty acids stored in monogastric animals largely indicates that the lipid and fatty acid composition of poultry eggs can be altered by diet [37]. Hence, eggs can be an important source of n-3 PUFA when laying hens are fed a diet containing a high level of n-3 PUFA [11,38]. Numerous fatty acid desaturases play key roles in synthesizing PUFA.…”
Section: Discussionmentioning
confidence: 99%
“…Lutein and phenolic compounds (particularly flavonoids) are potent antioxidants due to their free radical quenching activities [32,44]. Grčević et al [38] reported that the addition of marigold powder (rich in lutein) to the laying hens' feed significantly increased egg lutein content and preserved the high content of DHA in the yolks. Loetscher et al [15] provided broilers with a diet supplemented with 2.5% U. dioica and found that the tocopherols content of the breast meat was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Darkening of egg yolk and chicken skin has been reported previously (Fenwick and Curtis, 1980 ) and therefore was expected feeding Brassica co-products. Darker egg yolk and broiler skin is preferred in countries such as Mexico where pigments are intentionally added to feed to achieve that result (Grčević et al, 2018 ). Feeding Brassica cake and meal could spare the additional cost associated with including pigments in poultry diets for this purpose (Ponsano et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%